2022
DOI: 10.1037/ser0000572
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the impacts of exposure to potentially traumatic events on the mental health of public safety personnel: A rapid systematic scoping review.

Abstract: Police, firefighters, and emergency medical technicians and paramedics are frequently exposed to potentially traumatic events (PTE) in their work as public safety personnel (PSP). PTE are a risk factor for posttraumatic stress disorder, depression, anxiety, substance abuse, and suicidal ideation. This systematic rapid scoping review summarizes evaluation research on psychosocial interventions to reduce the negative consequences of exposure to work-related PTE on the mental health of PSP. Articles were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 91 publications
(272 reference statements)
0
6
0
Order By: Relevance
“…A greater focus on proactive programming may benefit CW wellbeing (16). Moreover, proactive programs have been shown to enhance resilience and well-being and reduce emotional exhaustion, mental concerns, and burnout in CWs (105,106). Many PSPs report a motivation to learn skills to manage their mental health symptoms, indicating the appropriateness of skills-based and resilience-building proactive treatments (66).…”
Section: Integration Of Proactive Interventionsmentioning
confidence: 99%
“…A greater focus on proactive programming may benefit CW wellbeing (16). Moreover, proactive programs have been shown to enhance resilience and well-being and reduce emotional exhaustion, mental concerns, and burnout in CWs (105,106). Many PSPs report a motivation to learn skills to manage their mental health symptoms, indicating the appropriateness of skills-based and resilience-building proactive treatments (66).…”
Section: Integration Of Proactive Interventionsmentioning
confidence: 99%
“…Petrie et al found a decrease of prevalence rates over time and explained this finding with (1) an increase in underreporting of PTSD due to stigma or fear of organizational consequences, and (2) an increase in awareness of mental health issues in ambulance or rescue stations ( 17 ). We like to add to these apparently contradicting arguments that there is generally weak evidence for work-place interventions in paramedics ( 67 , 73 ). Especially, post-incidence support processes show contradictory results ( 67 ).…”
Section: Discussionmentioning
confidence: 96%
“…It is imperative to continue efforts to implement mental health initiatives for ambulance personnel. These include standardized pre-employment selection processes, on-the-job training or education concerning mental health and well-being, and social embeddedness ( 66 , 67 ). A further target should be the experienced emotional burden in conjunction with the physical and mental support of affected persons, because the lack of distancing might be responsible that paramedics were more affected with PTSD symptoms than any other group of professional first responders ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moving to another important and underserved service-seeking group-Public Safety Personnel, including police, firefighters, emergency medical technicians, and paramedics are examined in multiple samples for a systematic rapid scoping review by Corthésy-Blondin et al (2022). The parameters of this rapid systematic scoping review allowed for and yielded a final group of 18 studies, from two databases published during a recent 8-year period.…”
Section: Evaluative Responsesmentioning
confidence: 99%